<span>Area of the upper rectangle = x(16 - 6) = 10x </span>yd²<span>
Area of the bottom rectangle = 6(x + 6) = 6x + 36 </span>yd²<span>
Total area = 10x + 6x + 36 = 16x + 36 yd</span>²
Answer:
4.2
Step-by-step explanation:
First I did 54 divided by 3 which is 18. Then I found the square root of 18.
Answer:
3 ( x-1) (x+1) is the factored form
zeros are x=1, -1
Step-by-step explanation:
3x^2-3
Factor out a 3
3 ( x^2 -1)
What is inside the parentheses is the difference of squares
( a^2 -b^2) = ( a-b)(a+b)
3 ( x-1) (x+1)
To find the zeros, set this equal to zero
3 ( x-1) (x+1) =0
Using the zero product property
x-1 =0 x+1 =0
x=1, x=-1
Answer
14 degrees
Step-by-step explanation:
Answer:
TERO BAU KO TAUKO MULA JEPAITE SODCHOS